High thermal conductivity in cubic boron arsenide crystals - Li, Sheng; Zheng, Qiye; Lv, Yinchuan; Liu, Xiaoyuan; Wang, Xiqu; Huang, Pinshane Y.; Cahill, David G.; Lv, Bing (Science (American Association for the Advancement of Science), 2018)
Thermal management becomes increasingly important as we decrease device size and increase computing power. Engineering materials with high thermal conductivity, such as boron arsenide (BAs), is hard because it is essential to avoid defects and impurities during synthesis, which would stop heat flow. Three different research groups have synthesized BAs with a thermal conductivity around 1000 watts per meter-kelvin: Kang et al. , Li et al. , and Tian et al. succeeded in synthesizing high-purity BAs with conductivities half that of diamond but more than double that of conventional metals (see the Perspective by Dames). The advance validates the search for high-thermal-conductivity materials and provides a new material that may be more easily integrated into semiconducting devices. Science , this issue p. 575 , p. 579 , p. 582 ; see also p. 549 Boron arsenide has an ultrahigh thermal conductivity, making it competitive with diamond for thermal management applications. The high density of heat generated in power electronics and optoelectronic devices is a critical bottleneck in their application. New materials with high thermal conductivity are needed to effectively dissipate heat and thereby enable enhanced performance of power controls, solid-state lighting, communication, and security systems. We report the experimental discovery of high thermal conductivity at room temperature in cubic boron arsenide (BAs) grown through a modified chemical vapor transport technique. The thermal conductivity of BAs, 1000 ± 90 watts per meter per kelvin meter-kelvin, is higher than that of silicon carbide by a factor of 3 and is surpassed only by diamond and the basal-plane value of graphite. This work shows that BAs represents a class of ultrahigh–thermal conductivity materials predicted by a recent theory, and that it may constitute a useful thermal management material for high–power density electronic devices.